First assessment of the pore water composition of Rupel Clay in the Netherlands and the characterisation of its reactive solids. Issue 3 (15th July 2016) - Behrends, Thilo; van der Veen, Iris; Hoving, Alwina; Griffioen, Jasper
Abstract: The Rupel Clay member in the Netherlands largely corresponds to the Boom Formation in Belgium, and this marine, clay-rich deposit is a potential candidate to host radioactive waste disposal facilities. Prediction of the speciation of radionuclides in Rupel Clay pore water and their retardation by interactions with Rupel Clay components requires knowledge about the composition of Rupel Clay pore water, the inventory of reactive solids and understanding of interactions between Rupel Clay and pore water. Here, we studied Rupel Clay material which was obtained from cores collected in the province of Zeeland, the Netherlands, and from drilling cuttings retrieved from a drilling in the province of Limburg, the Netherlands. Pore water was obtained by mechanical squeezing of Rupel Clay material from Zeeland. Additionally, anaerobic dilution experiments were performed in which the clay material was suspended with demineralised water or a 0.1M NaHCO3 solution. Solid-phase characterisation included determination of carbon, nitrogen and sulphur contents, measurement of cation exchange capacity (CEC) and sequential extraction of iron phases. In contrast to the pore water in Belgian Boom Clay, pore water collected from the location in Zeeland has a higher salinity, with chloride concentrations corresponding to 70–96% of those in seawater. The high chloride concentrations most likely result from the intrusion of ions from saline waters above the Rupel Clay in Zeeland. Cation exchange during salinisation might account for the observed deficit of marine cations (Na, K, Mg) and excess of Ca concentrations, in comparison with seawater. The measured CEC values at both locations in the Netherlands vary between 7 and 35 meq(100g) −1 and are, for most samples, in the range reported for Boom Clay in Belgium (7–30meq(100g) −1 ). Pore water and solid-phase composition indicate that Rupel Clay from Zeeland has been affected by oxidation of pyrite or other Fe(II)-containing solids. When coupled to the dissolution of calcium carbonates, oxidation of pyrite can account for the elevated sulphate and calcium concentrations measured in some of the pore waters. The relatively low concentrations of pyrite, organic carbon and calcite in the Rupel Clay in Zeeland, in comparison to Limburg, might be an indicator for an oxidation event. Higher contents of dithionite-extractable Fe in Rupel Clay in Zeeland (0.7–2.6mg Fe / g clay) than in Limburg (0.4–0.5mg Fe / g clay) might also be a consequence of the oxidation of Fe(II) minerals. Oxidation in the past could have accompanied partial erosion of Rupel Clay in Zeeland before deposition of the Breda Formation. However, indications are given that oxidation occurred in some of the pore waters after sampling and that partial oxidation of the cores during storage cannot be excluded. Results from dilution experiments substantiate the influence of equilibration with calcium carbonates on pore water composition. Furthermore, removal of dissolved sulphate upon interaction with Rupel Clay has been observed in some dilution experiments, possibly involving microbial sulphate reduction.